Modele myślenia o reformowaniu oświaty - Kwieciński, Zbigniew (Wydawnictwo Naukowe UAM, 2012)
Author analyses seven main models of reflections (paradigms, patterns) on educational reforming: pedagogism, reformism, systemic approach, dialectic approach, scepticism (sociologism), deschool-ing, eclectism (simulated reforms). The author presents main differences and similarities.
Models of reflection on educational reforming